PHARMACEUTICAL CARE FOR INSULIN-DEPENDENT PATIENTS: AN EXPERIENCE REPORT: AN EXPERIENCE REPORT - Freitas Martins, Marília Cláudia; do Vale Bezerra, Priscilla Karilline (Cadernos ESP, 2025)
Objective: The report aims to describe the experience of a pharmacist resident in home visits to insulin-dependent patients. Methods: This is a descriptive study with a qualitative approach, conducted between November 2024 and January 2025, with patients registered as insulin-dependent at the primary health care unit where the resident worked. The activity was carried out through follow-up to understand the users' knowledge about insulin treatment. Results: During the study, it was possible to identify the patients' level of understanding regarding the correct use of insulin, their lack of knowledge about proper medication storage, and the need for guidance on daily blood glucose monitoring. Final considerations: The study emphasizes the importance of the pharmacist in caring for diabetic patients, as this professional plays a key role in providing guidance on pharmacotherapy, thus contributing to the improvement of patients' glycemic control.
Keywords: Pharmaceutical Services; Insulin; Diabetes Mellitus